Strengthening Quality Culture in Education Services in Madrasah: Penguatan Budaya Mutu dalam Pelayanan Pendidikan di Madrasah - Musfiqon (Halaqa: Islamic Education Journal, 2020)
This paper supports the discussion of the concept of strengthening educational culture for managers of educational institutions. In this paper, a strategy to foster a culture of educa- tional quality is also examined so that the quality of madrasah education becomes better, both in terms of inputs, processes and results. The quality strategy in education in schools begins with a number of steps, namely (1) determining quality criteria, (2) building qual- ity commitments, (3) developing cultural quality, (4) developing the quality of educational services, and (5) improving the quality of school culture. The form of quality culture-based services can be done by improving academic quality that complements the developed competency standards, content standards, process standards, and adjusted standards. These four components, if implemented optimally, will be an indicator of descriptors of educational services in quality-based madrasas. Quality strategies in education services in madrasas need to start with a number of steps, namely (1) Find Support, (2) Support Support, (3) build a quality culture , (4) building the quality of education services, and (5) improving the quality of madrasa culture.